IDENTIFIKASI FORMALIN PADA PRODUK HASIL PERIKANAN BAGI SISWA MADRASAH ALIYAH MIFTAHUL ULUM SUNGAI LUMPUR KABUPATEN OGAN KOMERING ILIR - Sofian Sofian; Indah Anggraini Yusanti; Fitra Mulia Jaya; Neny Rochyani; Rih Laksmi Utpalasari (Jurnal Abdi Insani, 2022)
Cengal District, Ogan Komering Ilir Regency is a coastal area that has considerable fishery potential because it is surrounded by inland and coastal public waters. Difficult location access causes the distribution of fishery raw materials outside the region to be a constraint for the community considering the limited shelf life. The use of preservatives in fishery products such as formalin is often found in the market which is very dangerous if consumed by humans continuously in small quantities. This community service activity aims to provide information to the community through the role of students and teachers of Miftahul Ulum Private Madrasah Aliyah Sungai Lumpur about the dangers of consuming fishery products that contain harmful preservatives such as borax and formalin. This activity was carried out using the direct testing method of several fishery products involving students and teachers. Testing the content of formalin in fishery products is simple by using a formalin test kit. The test sample can be observed directly by changing the color of the chemical reaction of the test sample. The results of this activity directly increase students' knowledge about the dangers of consuming fishery products that contain ingredients that are harmful to health. In addition, students can physically distinguish fishery products that use hazardous materials and can directly test the hazardous content in fishery products. Through this community service activity, the community can reduce the use of hazardous materials as food preservatives and avoid consuming various processed fish products that are less healthy.